KONTEMPLASI DAMPAK PASCA PANDEMI COVID-19 TERHADAP KEANEKARAGAMAN HAYATI - Firmansyah (Gunung Djati Conference Series, 2023)
The Covid-19 pandemic has had an impact on all interrelated lines of life. Biodiversity is one of the compensations for the domino impact of a series of life-line destruction. The lockdown policy and restrictions on community activities for a long time causes forests and wild animals to tend to have small disturbance values. However, when most of business condition are come down which in causes increased unemployment due to abnormal business wheels, there is potential for biodiversity destruction. The threat of damage to biodiversity is a domino effect of increased hunting of wild animals and increase wildlife trade. An anticipatory movement carried out by biology student organizations and NGO’s through monitoring illegal wildlife trade, increasing conservation research and training activities in protected and non-protected biodiversity areas and increasing community participation which will greatly help maintain biodiversity conservation at the national to global level become a priority for the conservation of biodiversity sustainability.